Ocular Toxoplasmosis in Tropical Areas: Analysis and Outcome of 190 Patients from a Multicenter Collaborative Study. (17th November 2018) - Huang, Philemon K.; Jianping, Chen; Vasconcelos-Santos, Daniel Vitor; Arruda, Jacqueline Souza Dutra; Dutta Majumder, Parthopratim; Anthony, Eliza; Ganesh, Sudha K.; Biswas, Jyotirmay; Ling, Ho Su; Teoh, Stephen C.; Agrawal, Rupesh
ABSTRACT: Purpose : To describe clinical findings and outcomes for ocular toxoplasmosis in an international multicenter collaborative study. Methods : Retrospective analysis of 190 patients diagnosed with ocular toxoplasmosis from three study sites (Brazil, India, and Singapore). Results : There were 93 (48.9%) females with a mean age of 32.8 years. The most common symptoms were isolated blurring of vision (36.8%), followed by blurring of vision with floaters (21.1%). Treatment regimens varied largely from monotherapy to multiple combination therapies. Final visual acuity of ≥20/40 was achieved in 106 (74.2%) patients. In a median follow-up period of 31 weeks (range 12–749 weeks), 83/190 (43.7%) patients suffered a relapse. Conclusions : There appears to be geographical variation in the presentation of ocular toxoplasmosis. Compared to previous studies, we did not observe the '"dual peak" phenomenon of chronic and active disease based on age at presentation, and there was less bilateral and macular involvement (but more peripheral involvement).